Daredevils - Vestal, Shawn (Penguin Press, 2016)
Caught dating a boy of another faith by her devout Mormon parents, 1970s teenager Loretta is married off to a fundamentalist as his second wife and runs away with his nephew and a part-Native American friend to search for a cache of gold and freedom outside their strict community.